Two New Lycodine Alkaloids from Lycopodiastrum casuarinoides. Issue 12 (December 2014) - Wu, Ji‐Chun; Wang, Qiu‐Yue; Tao, Ying‐Jiang; Jiang, Jin‐He; Liu, Ying; Huang, Guo‐Li; Zhan, Rui; Liu, Bo; Chen, Ye‐Gao
Abstract Two new lycodine alkaloids, 11β‐methoxyhuperzine B (1) and 16‐oxohuperzinine (2), together with seven known ones, huperzinine N‐oxide, huperzine D, casuarinine A, huperzine B, casuarinine B, huperzinine, and N‐methyllycodine, were isolated from whole plants of Lycopodiastrum casuarinoides. Their structures were elucidated by spectroscopic methods, including NMR and MS experiments.